Conformational study of L-methionine and L-cysteine derivatives through quantum chemical calculations and 3JHH coupling constant analyses - Silva, Weslley G. D. P.; Braga, Carolyne B.; Rittner, Roberto (Beilstein Journal of Organic Chemistry, 2017)
The understanding of the conformational behavior of amino acids and their derivatives is a challenging task. Here, the conformational analysis of esterified and N-acetylated derivatives of L-methionine and L-cysteine using a combination of 1H NMR and electronic structure calculations is reported. The geometries and energies of the most stable conformers in isolated phase and taking into account the implicit solvent effects, according to the integral equation formalism polarizable continuum model (IEF−PCM), were obtained at the ωB97X-D/aug-cc-pVTZ level. The conformational preferences of the compounds in solution were also determined from experimental and theoretical 3JHH coupling constants analysis in different aprotic solvents. The results showed that the conformational stability of the esterified derivatives is not very sensitive to solvent effects, whereas the conformational equilibrium of the N-acetylated derivatives changes in the presence of solvent. According to the natural bond orbital (NBO), quantum theory of atoms in molecules (QTAIM) and noncovalent interactions (NCI) methodologies, the conformational preferences for the compounds are not dictated by intramolecular hydrogen bonding, but by a joint contribution of hyperconjugative and steric effects.
Keywords: amino acid derivatives; conformational analysis; cysteine; methionine; NMR spectroscopy; quantum chemical calculations